Convenient synthesis of enantiomerically pure (R)-mexiletine using hydrolytic kinetic resolution method - Sasikumar, Murugesan; Nikalje, Milind D.; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2009)
Enantiopure (R)-mexiletine was prepared in a simple and practical way using hydrolytic kinetic resolution method of terminal epoxide by Jacobsen catalyst. High enantiomeric purity (98% ee) was achieved and the method is well amenable to industrial scale-up. (C) 2009 Elsevier Ltd. All rights reserved.

Facile enantioselective synthesis of enantiomerically pure (R)-phenoxybenzamine hydrochloride using the hydrolytic kinetic resolution method - Nikalje, Milind D.; Sasikumar, Murugesan; Muthukrishnan, Murugan (Tetrahedron-Asymmetry, 2010)
A practical and highly efficient enantioselective synthesis of (R)-phenoxybenzamine hydrochloride has been described for the first time using Jacobsen's hydrolytic kinetic resolution of a terminal epoxide as a key step and source of chirality. (C) 2010 Elsevier Ltd. All rights reserved.